ECONOMIC AND STATISTICAL ASSESSMENT AS A TOOL FOR QUALITY MANAGEMENT OF LIVING FOR SUSTAINABLE DEVELOPMENT OF THE REGION - S. Gagarina; N. Chausov (Вестник университета)
The article shows that the quality of life of the population control problem has become paramount, and results of the evaluation, describing the current status, dynamics and trends are the basis for the formation of social and economic policy of the Russian Federation subjects. Methodical approaches to the assessment of quality of life. On the example of the Kaluga region held economic and statistical evaluation of the quality of life on the basis of objective indicators.